THE EFFECT OF PROJECT-BASED LEARNING ON STUDENTS VOCABULARY ACHIEVEMENT AT SECOND GRADE OF ISLAMIC JUNIOR HIGH SCHOOL - Mufidah Kholis; Imam Nur Aziz (JEET, Journal of English Education and Technology, 2020)
This article aims to find out the empirical evidence of enriching students’ vocabulary through project-based learning (PjBL). Project-based learning (Project Based Learning) is a learning method that uses projects as the core of learning. This is an innovative learning method that involves project work where students work independently in constructing their learning and culminating in real products. The researcher uses experiments and samples are students of the second grade of junior high in Sugihwaras Bojonegoro. The result shows that the pretest average of the experimental group is 2.100. The post-test average of the experimental group is 2.500. The obtained t-test is 15, 20, whereas the t-table is 2, 02 for a = 5%. The t-test score is higher than the t-table (15, 20> 2, 02). It means that Ha is accepted while Ho is rejected. Since the t-test score was higher than the t-table, that can include project-based learning were an effective model in enriching students’ vocabulary of English learning process at the second grade of Islamic Junior High in Sugihwaras Bojonegoro.